Coinfection of Hepatitis B and C Viruses and Risk of Hepatocellular Carcinoma: Systematic Review and Meta-analysis - Abdullah A. Awadh; Abdulrahman A. Alharthi; Basil A. Alghamdi; Seraj T. Alghamdi; Mohammed K. Baqays; Ibrahim S. Binrabaa; Israa A. Malli (Journal of Global Infectious Diseases)
Introduction: Hepatitis B and C are viral infections causing chronic liver inflammation and, when left untreated, lead to cirrhosis and a risk for hepatocellular carcinoma, the most common type of primary liver cancer with high mortality. The hepatitis B virus-hepatitis C virus (HBV-HCV) coinfection leads to a faster progression to advanced liver diseases and higher hepatocellular carcinoma (HCC) risk than monoinfection. Unlike the relative risk for HCC due to either HBV or HCV, no recent analysis of the risk for HBV-HCV coinfection exists. Methods: Based on PRISMA recommendations and guidelines, we developed a search strategy by combining the keywords (“hepatitis B”) and (“hepatitis C”) and (“hepatocellular carcinoma” or “liver cancer”). First, we performed a title and abstract screening and, later, a full-text screening. We extracted the demographic characteristics, such as gender, age, study design, sample size, country, and biomarkers of hepatitis B surface antigen (HBsAg), HBV DNA, HBeAg, anti-HCV, and HCV RNA. The data were assessed for quality, and the Review Manager software was used for the meta-analysis. Results: We included 63 studies. The pooled analysis showed that the risk of HCC was significantly higher in the case-cohort who were positive for HBsAg (odds ratio [OR] = 9.70 [3.75, 25.12], P = 0.0001), HBV DNA or HBeAg (OR = 22.77 [10.00, 51.88], P = 0.0001), HBV and HCV coinfection (OR = 46.07 [26.33, 80.60], P = 0.0001) than the control cohort. Conclusion: Chronic HBV and HCV infections are major risk factors for HCC, and their coinfection was significantly associated with an increased risk of HCC than monoinfection.